Perfil epidemiológico do hiv/aids nos cinco municípios mais populosos do interior do estado do Amazonas - Costa, Naymê Pereira (Brasil, 2024)
Human Immunodeficiency Virus (HIV) is a retrovirus that causes Acquired Immunodeficiency Syndrome (AIDS), a chronic disease that attacks and weakens the human immune system. Since its discovery in 1983, HIV has been a major public health concern due to its ability to attack and weaken the immune system, specifically CD4+ T cells, which play a crucial role in the body's immune response. The work aims to evaluate the "Epidemiological Profile of HIV/AIDS in the five most populous municipalities in the interior of the State of Amazonas", describing the epidemiological situation in the municipalities of Itacoatiara, Manacapuru, Parintins, Coari and Tefé in the period from 2019 to 2023. Epidemiological data were collected from the DATASUS database and analyzed in terms of education, gender, race, age range, in addition to the prevention and treatment strategies implemented. In Parintins, the prevalence of HIV/AIDS is higher among men and young people aged 15 to 24 years old, especially in the brown population with complete high school, indicating the need for prevention strategies focused on risk behaviors and education. Itacoatiara shows a male predominance, but with a significant increase in female notifications in 2023, highlighting the importance of improving access to health services. Manacapuru also has a high prevalence among men and young people, with an increase in 2021 and 2022 and a decrease in 2023, suggesting improvements in health policies. In Coari, prevalence is high among young and brown people, with cases increasing in 2021 and a subsequent drop, underscoring the continued need for health interventions and education. Tefé exhibits patterns similar to those of other cities in Amazonas, with a high prevalence among men and young people. The study concludes that more inclusive public policies and coordinated actions are needed to combat stigma and discrimination, aiming to reduce the incidence and impact of HIV/AIDS in the region.